Respuesta agronómica del maíz hibrido ‘s – 810´ en presencia de dosis y épocas de aplicación de un promotor de crecimiento a base de un extracto de algas marinas - Murillo Soto, Carlos (2011)
On the grounds of the Estate "New Island" belonging to Mr. Antenor Murillo Contreras, located one kilometer from the parish Bejucal Island, Canton Baba, a trial was tested doses and times of application of Fartum growth promoter in maize hybrid 'S - 810', in order to evaluate the agronomic response and grain yield of hybrid Fartum present, identify the dose and application time of the growth promoter to maximize grain yield, determine the efficiency of Fartum; and analyzing economic treatments. The treatments were constituted by the dose and timing of application of Fartum were: 3.0 l / ha applied at 21 dap and 45 das, 1.5 l / ha at 21 and 45 das, 45 l / ha applied at 21 dap and 45 das, 2.25 L / ha applied at 21 and 45 das, and 6.0 l / ha applied at 21 dap and 45 das, 3.0 l / ha applied at 21 and 45 das, also included a control lacking the growth promoter for a total and 10 treatments. Experimental design was used randomized complete blocks with three replications. The experimental plot was composed of 6 rows of 6 m in length separated 0.70m, giving an area of 25.7 m2. The population density was 71,428 plants per hectare........